Influence of premixed chlorine salt on the pore characteristics of cement-based hardened grout containing a large amount of bentonite. (16th May 2023) - Niu, Xiaohong; Feng, Guorui; Han, Yanna; Bezuijen, Adam; Qi, Tingye; Bai, Jinwen
Highlights: LF-NMR tests are complemented by low-pressure CO2 and N2 adsorption tests. According to the pore size, pores in the hardened grouts are divided into five types. Unit volume variation is introduced to reveal the effect of chloride on pore structure. Controlling factors of the chloride effect on the volume of various pores are revealed. Differences in the effect of NaCl and CaCl2 on pore structure are analyzed. Abstract: Moderate content of premixed chlorine salt could improve the fluidity and strength of cement-based grouts containing a large amount of bentonite, while its effect on pore structure is still unclear. In this study, pore characteristics were systematically described by low-field NMR combined with low-pressure CO2 and N2 adsorption. Pores were classified into five types according to their size to clarify the effect of chloride content, curing time, and chloride type (NaCl or CaCl2 ) on various pore volumes. This was further analyzed by the introduction of unit volume variation (U). Results show that the volume of inter gel pore (2–10 nm) and middle capillary pore (50–1000 nm) increases with the increase of chloride content while that of fine (10–50 nm) and large (>1000 nm) capillary pore decreases. The inter gel pore volume and fine capillary pore volume depend on C–S–H content and surfactant micelles number, respectively. The volume of middle and large capillary pores is mainly affected by the hydration product content. For intra sheet pores (<2 nm), their volumes show an inverted "N" shape with the increase of NaCl content and a "U" shape for CaCl2, which is mainly related to the ettringite dissolution and nano-SiO2 dispersion. The chloride content and curing time also have a large reduction effect on the U of intra sheet pores, fine and large capillary pores. Furthermore, CaCl2 contributes more than NaCl to the development of pore structure, especially for inter gel pores and middle capillary pores.